Successful application of thrombolysis and angioplasty in case of mechanical aortic valve and coronary graft thrombosis - Norkienė, Ieva; Kažukauskienė, Ieva; Samalavičius, Robertas; Ručinskas, Kęstutis (Acta medica Lituanica, 2016)
Prosthetic valve thrombosis (PVT) is a rare and fatal complication requiring immediate treatment. Optimal management of the left-sided obstructive PVT is still controversial and depends on patient’s status, estimated risk of surgery, thrombus location and size, and clinician’s experience. We report a case of a 71-year-old woman, presenting with signs of cardiogenic shock. Transesophageal echoscopy was used to diagnose acute obstructive thrombosis of the mechanical aortic valve. Concomitant coronary graft thrombosis was suspected due to signs of acute myocardial infarction. Thrombolysis with alteplase and subsequent stenting of the venous graft lead to successful resolution of the thrombotic lesions and a favourable patient outcome. Fibrinolytic therapy followed by angioplasty is a rational treatment alternative for inoperable or high risk patients in the case of concomitant mechanical valve and graft thrombosis.